Analisis Keterlibatan dan Respon Siswa dalam Menyelesaikan Soal Tidak Rutin Pada Materi Lingkaran Kelas VIII SMP - Yulita Kadinda Della; Marhadi Saputro; Wandra Irvandi (LPD IKIP PGRI Pontianak, 2023)
This research aims to determine students' involvement and responses in solving non-routine questions on circle material. The method used in this research is a qualitative descriptive method in the form of case study research. This research was carried out in class VIII of Santa Ursula Gunung Tamang Middle School involving 5 students as research subjects who were taken using Purposive Sampling techniques with the selected categories including one student with involvement and response in the good category, one student with involvement in the sufficient category, one student with involvement in the less category, one student with a response in the sufficient category and one student with a response in the less category. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that student involvement and response in the good category get a satisfactory score, namely a score above the KKM and can fulfill 4 indicators of problem solving in non-routine questions, student involvement and response in the adequate category get a value that is inversely proportional to where student involvement in the category enough to get a score above the KKM and can almost fulfill 4 indicators of problem solving in non-routine questions, while student responses in the sufficient category get a score below the KKM and can only fulfill several indicators of problem solving in non-routine questions, and student involvement and responses in the category get less grades which are both below the KKM and can only fulfill 2 problem solving indicators in non-routine question.